High-performance silicon-aluminum composite negative electrode material and preparation method and application thereof
By combining nanosilicon particles and aluminum-containing compounds with high-performance silicon/aluminum composite anode material prepared by low-speed ball milling, the problems of slow dynamics and poor mechanical stability of silicon-based batteries are solved, and the improvement of high energy density and fast charging performance is achieved.
Patent Information
- Application Number
- CN202510040784.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Due to the low electronic conductivity and huge volume changes in silicon-based batteries, the cycle performance and fast charging performance are poor. The existing modification methods weaken the advantages of silicon's high specific capacity, and the side reactions in the conductive carbon acceleration electrode reduce energy density.
High-performance silicon/aluminum composite anode material is prepared by low-speed ball milling with aluminum-containing compounds with high theoretical specific capacity and nanosilicon particles. The nanosilicon particles are uniformly attached to the frame structure of aluminum-containing compounds to form a negative electrode sheet with fast electrode kinetics and high mechanical stability.
It achieves high energy density, high power density and high fast charging performance, and improves the specific capacity, energy density, first-week Coulomb efficiency and cycling performance of lithium-ion batteries.
Smart Images

Figure CN119833615A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a high-performance silicon-aluminum composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon (Si) has ultra-high specific capacity (3580mAh / g), low lithiation potential (0.2~0.4V vs.Li + / L i), chemical properties are more stable than lithium metal and low cost, silicon-based batteries are expected to meet the actual use needs of high energy density and high safety.
[0003] However, silicon has very low electronic conductivity and huge volume changes, which make silicon's cycling performance and fast charging performance poor. To address these challenges, traditional methods such as modifying silicon to prepare composite materials such as SiC and SiO weaken the high specific capacity advantage of silicon; in addition, mixing non-electrochemically active substances such as solid electrolytes or conductive carbon with silicon to prepare composite silicon negative electrodes can enhance electrode kinetics, but conductive carbon with a high specific surface area will accelerate side reactions in the electrode and reduce the battery energy density.
[0004] The present invention proposes a high-performance silicon / aluminum composite negative electrode preparation technology, which aims to solve key challenges such as slow silicon negative electrode kinetics, poor electrode mechanical stability and interface side reactions, thereby realizing the practical application of high energy density, long cycle life and low-cost silicon-based batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a high-performance silicon-aluminum composite negative electrode material and a preparation method and application thereof in view of the defects of the prior art.
[0006] The present invention selects aluminum-containing compounds with high theoretical specific capacity (990 mAh / g), high conductivity and high ductility and nano-silicon particles to prepare high-performance silicon / aluminum composite negative electrode materials. The negative electrode sheet prepared using this material has fast electrode kinetics, high electrode mechanical stability, high energy density, high power density and high fast charging performance (maximum current density reaches 8.1 mA / cm -2 ), etc., and the negative electrode sheet containing the high-performance silicon-aluminum composite negative electrode material of the present invention is assembled into a lithium-ion battery, especially an all-solid-state lithium-ion battery, which can improve the battery's specific capacity, energy density, first-cycle coulomb efficiency and cycle performance.
[0007] The method for preparing a high-performance silicon-aluminum composite negative electrode material provided by the embodiment of the present invention is simple to operate, has low raw material and processing costs, and has great commercial prospects.
[0008] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a high-performance silicon-aluminum composite negative electrode material, the high-performance silicon-aluminum composite negative electrode material comprising: an aluminum-containing compound, and nano-silicon particles uniformly attached to a framework structure formed by the aluminum-containing compound;
[0009] The aluminum-containing compound includes: aluminum powder and / or lithium aluminum alloy;
[0010] The average particle size D of the aluminum-containing compound 50 Between 5μm and 60μm;
[0011] The mass of the nano-silicon accounts for 40% to 90% of the total mass of the high-performance silicon-aluminum composite negative electrode material;
[0012] The mass of the aluminum-containing compound accounts for 10% to 60% of the total mass of the high-performance silicon-aluminum composite negative electrode material;
[0013] The high-performance silicon-aluminum composite negative electrode material is obtained by low-speed ball milling of the nano silicon particles and the aluminum-containing compound.
[0014] Preferably, the aluminum-containing compound is in the shape of one or more of a rod, a line or an irregular shape;
[0015] The average particle size D of the nano-silicon 50 1nm~200nm;
[0016] The general chemical formula of the lithium aluminum alloy is Li x A l, where 0<x≤1;
[0017] The average particle size D of the high performance silicon-aluminum composite negative electrode material 50 5μm~60μm;
[0018] The low-speed ball milling includes: placing the nano-silicon particles and the aluminum-containing compound in a ball mill, ball milling at a speed of 150rpm to 200rpm for 7 minutes to 10 minutes, stopping the ball milling for 3 minutes to 5 minutes, and then continuing the ball milling for 7 minutes to 10 minutes, repeating the ball milling process, and ball milling for a total of 1 hour to 2 hours.
[0019] In a second aspect, an embodiment of the present invention provides a method for preparing the high-performance silicon-aluminum composite negative electrode material described in the first aspect, the preparation method comprising: ball milling nano-silicon particles and an aluminum-containing compound at a low speed to obtain a high-performance silicon-aluminum composite negative electrode material;
[0020] Wherein, the aluminum-containing compound comprises aluminum powder and / or lithium aluminum alloy; the general chemical formula of the lithium aluminum alloy is Li x A l, wherein 0<x≤1; the lithium aluminum alloy is obtained by pre-lithiation treatment.
[0021] Preferably, the mass ratio of the nano-silicon particles to the aluminum-containing compound is 4:6 to 9:1;
[0022] The particle size D of the aluminum-containing compound 50 Between 5μm and 60μm;
[0023] The rotation speed of the low-speed ball mill is 150 rpm to 200 rpm. The ball mill is performed for 7 to 10 minutes, and then the ball mill is stopped for 3 to 5 minutes, and then the ball mill is continued for 7 to 10 minutes. The ball milling process is repeated for a total of 1 to 2 hours.
[0024] Preferably, the pre-lithiation treatment comprises:
[0025] dissolving metallic lithium in an organic solvent to obtain a pre-lithiation solution;
[0026] Adding aluminum powder to the pre-lithiation solution, mechanically mixing and stirring to obtain a mixed solution;
[0027] The solid substance obtained after filtering the mixed solution is washed at least twice with dimethyltetrahydrofuran, and then vacuum dried at 80° C. to 100° C. for 8 to 12 hours to obtain the lithium aluminum alloy;
[0028] The organic solvent is a biphenyl-dimethyltetrahydrofuran solution formed by dissolving biphenyl in dimethyltetrahydrofuran; the molar ratio of the metallic lithium to the biphenyl in the organic solvent is 1:2 to 1:0.5;
[0029] The general chemical formula of the lithium aluminum alloy is Li x A l, where 0<x≤1;
[0030] The particle size D of the lithium aluminum alloy 50 Between 5μm and 60μm.
[0031] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the high-performance silicon-aluminum composite negative electrode material described in the first aspect above.
[0032] In a fourth aspect, an embodiment of the present invention provides a method for preparing the negative electrode sheet described in the third aspect, the method comprising: mixing the high-performance silicon-aluminum composite negative electrode material described in the first aspect with a first binder and a solvent to form a negative electrode slurry, then coating the negative electrode slurry on a current collector, and sequentially baking, rolling, and slitting to obtain a negative electrode sheet;
[0033] The first binder includes: one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), polyacrylic acid, polytetrafluoroethylene (PTFE), and polymethyl methacrylate (PMMA);
[0034] The solvent includes: any one of N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO);
[0035] The current collector comprises: any one of copper foil, stainless steel foil, titanium foil or a flexible composite current collector.
[0036] In a fifth aspect, an embodiment of the present invention provides a method for preparing the negative electrode sheet described in the third aspect, the method comprising: dry-mixing the high-performance silicon-aluminum composite negative electrode material described in the first aspect with a second binder, and then performing a roll-pressing process to obtain a negative electrode sheet;
[0037] The second binder includes polytetrafluoroethylene (PTFE).
[0038] In a sixth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect above, or the negative electrode sheet prepared by the preparation method described in the fourth aspect above, or the negative electrode sheet prepared by the preparation method described in the fifth aspect above.
[0039] Preferably, the lithium-ion battery includes: a liquid lithium-ion battery, a semi-solid lithium-ion battery or an all-solid lithium-ion battery.
[0040] The embodiment of the present invention provides a high-performance silicon-aluminum composite negative electrode material and a preparation method and application thereof. The high-performance silicon-aluminum composite negative electrode material is obtained by ball milling a micron-sized aluminum compound with nano-sized silicon particles at a low speed, so that the nano-silicon particles are evenly dispersed on a frame formed by aluminum powder or lithium-aluminum alloy. The negative electrode sheet prepared using the high-performance silicon-aluminum composite negative electrode material has fast electrode kinetics, high electrode mechanical stability, high energy density, high power density and high fast charging performance (maximum current density reaches 8.1 mA / cm -2 ), etc., and the negative electrode sheet containing the high-performance silicon-aluminum composite negative electrode material of the present invention is assembled into a lithium-ion battery, which can improve the battery's specific capacity, energy density, first-cycle coulomb efficiency and cycle performance.
[0041] In addition, by adopting the pre-lithiation method provided in an embodiment of the present invention, aluminum powder is pre-lithiated to obtain a lithium-aluminum alloy, and low-speed ball milling is performed with nano-scale silicon particles to obtain a high-performance silicon-aluminum composite negative electrode material, wherein the pre-supplemented lithium can make up for the lack of active lithium during the battery cycle, and more significantly improve the initial coulombic efficiency and cycle performance of the battery.
[0042] The method for preparing a high-performance silicon-aluminum composite negative electrode material provided by the embodiment of the present invention is simple to operate, has low energy consumption by low-speed ball milling, low raw material and processing costs, and has great commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic structural diagram of a high-performance silicon-aluminum composite negative electrode material provided in an embodiment of the present invention.
[0044] Figure 2 The graph is a cycle curve of the all-solid-state lithium-ion battery of Example 1, Example 2 and Comparative Example 2 of the present invention.
[0045] Figure 3 It is a comparison chart of the first-cycle coulombic efficiency and the capacity retention rate after 50 cycles of the all-solid-state lithium-ion batteries assembled in Examples 1-2 of the present invention and Comparative Examples 1-7.
[0046] Figure 4 This is a scanning electron microscope (SEM) image of the surface of the negative electrode plate of the all-solid-state lithium-ion battery of Example 1 of the present invention after 50 cycles.
[0047] Figure 5 This is a SEM image of the surface of the negative electrode plate of the all-solid-state lithium-ion battery of Comparative Example 2 of the present invention after 50 cycles. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0050] The embodiment of the present invention provides a high-performance silicon-aluminum composite negative electrode material, comprising: an aluminum-containing compound, and nano-silicon particles uniformly attached to a framework structure formed by the aluminum-containing compound; the average particle size D of the high-performance silicon-aluminum composite negative electrode material is 50 5μm~60μm.
[0051] The aluminum-containing compounds include aluminum powder and / or lithium aluminum alloy; the general chemical formula of lithium aluminum alloy is Li x A l, where 0<x≤1.
[0052] The aluminum-containing compound may be in the form of one or more of a rod, a line or an irregular shape.
[0053] Average particle size D of aluminum-containing compounds 50 The average particle size D of the aluminum-containing compound of the present invention is between 5 μm and 60 μm, and can be any value within the above range, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable. 50 It is preferably 40 μm to 60 μm.
[0054] The present invention adopts the average particle size D 50 Micron-sized aluminum powder between 5μm and 60μm can more easily serve as a structural framework to adapt to the volume changes of nano-silicon particles during the charging and discharging process, while ensuring energy density.
[0055] The mass of the aluminum-containing compound accounts for 10% to 60% of the total mass of the high-performance silicon-aluminum composite negative electrode material, and can be any value within the above range, for example: 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] The average particle size of nano silicon particles is D 50 1nm~200nm; can be any value within the above range, for example: 1nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, etc., but is not limited to the listed values, other values not listed within the numerical range are also applicable. The particle size of the nano silicon particles is relatively uniform, preferably the particle size D 50 is 200nm.
[0057] The mass of nano-silicon particles accounts for 40% to 90% of the total mass of the high-performance silicon-aluminum composite negative electrode material, and can be any value within the above range, for example: 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] The high-performance silicon-aluminum composite negative electrode material provided in the embodiment of the present invention is obtained by low-speed ball milling of nano silicon particles and aluminum-containing compounds; wherein the low-speed ball milling is ball milling at a speed of 150 rpm to 200 rpm for 7 minutes to 10 minutes, stopping the ball milling for 3 minutes to 5 minutes, and then continuing the ball milling for 7 minutes to 10 minutes, repeating the ball milling process, and ball milling for a total of 1 hour to 2 hours. In the ball milling process, zirconium oxide balls are used as ball milling media, and the material-ball ratio is 20:1.
[0059] The high-performance silicon-aluminum composite negative electrode material provided in an embodiment of the present invention forms a framework structure of the aluminum-containing compound by low-speed ball milling, and the nano-silicon particles are uniformly dispersed and attached to the framework formed by the aluminum-containing compound during the low-speed ball milling process. The structural schematic diagram of the high-performance silicon-aluminum composite negative electrode material is as shown in FIG. Figure 1 As shown, it can be seen that nano-silicon particles are evenly dispersed and attached on the framework formed by the aluminum-containing compound, and the aluminum-containing compound forms an ion / electron transmission channel.
[0060] The embodiment of the present invention provides a method for preparing the above-mentioned high-performance silicon-aluminum composite negative electrode material, comprising: low-speed ball milling of nano-silicon particles and aluminum-containing compounds to obtain a high-performance silicon-aluminum composite negative electrode material.
[0061] The aluminum-containing compound includes aluminum powder and / or lithium aluminum alloy. The general chemical formula of lithium aluminum alloy is Li x A l, where 0<x≤1.
[0062] The mass ratio of nano silicon particles to aluminum-containing compounds is 4:6 to 9:1.
[0063] Particle size D of aluminum-containing compounds 50 Between 5μm and 60μm.
[0064] The speed of the low-speed ball mill is 150 rpm to 200 rpm. After 7 to 10 minutes of ball milling, the ball milling is stopped for 3 to 5 minutes, and then the ball milling is continued for 7 to 10 minutes. The ball milling process is repeated for a total of 1 to 2 hours. During the ball milling process, zirconia balls are used as ball milling media, and the material-to-ball ratio is 20:1.
[0065] The above lithium aluminum alloy is obtained by pre-lithiation treatment, and the pre-lithiation treatment specifically includes the following steps:
[0066] Step 1: dissolving metallic lithium in an organic solvent to obtain a pre-lithiation solution.
[0067] Step 2: adding aluminum powder to the pre-lithiation solution, mechanically mixing and stirring to obtain a mixed solution.
[0068] Step 3: The solid substance obtained after filtering the mixed solution is washed at least twice with dimethyltetrahydrofuran, and then vacuum dried at 80° C. to 100° C. for 8 to 12 hours to obtain a lithium aluminum alloy.
[0069] Specifically, the organic solvent is a biphenyl-dimethyltetrahydrofuran solution formed by dissolving biphenyl in dimethyltetrahydrofuran; the molar ratio of metallic lithium to biphenyl is 1:1.
[0070] The chemical formula of the obtained lithium aluminum alloy is Li x A l, where 0<x≤1; particle size D of lithium aluminum alloy 50 Between 5μm and 60μm.
[0071] An embodiment of the present invention provides a negative electrode plate, which includes the above-mentioned high-performance silicon-aluminum composite negative electrode material.
[0072] The embodiments of the present invention provide two methods for preparing the above-mentioned negative electrode sheets.
[0073] The first method for preparing the negative electrode sheet provided in the embodiment of the present invention comprises:
[0074] The high-performance silicon-aluminum composite negative electrode material is mixed with a first binder and a solvent to form a negative electrode slurry, which is then coated on a current collector, and then baked, rolled, and cut in sequence to obtain a negative electrode sheet.
[0075] Wherein, the first binder includes: one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), polyacrylic acid, polytetrafluoroethylene (PTFE), and polymethyl methacrylate (PMMA).
[0076] The mass ratio of the high-performance silicon-aluminum composite negative electrode material to the first binder is 85:15 to 95:5.
[0077] The solvent includes any one of N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO). The content of the solvent in the slurry is 20 wt % to 60 wt %, preferably 50 wt %.
[0078] The coating thickness is 60 μm to 150 μm.
[0079] The current collector includes: any one of copper foil, stainless steel foil, titanium foil or flexible composite current collector.
[0080] Coating, baking, rolling and slitting are all existing known methods. In addition, an inert atmosphere (high-purity argon) is required for protection during the processing of samples containing lithium aluminum alloys.
[0081] The second method for preparing the negative electrode sheet provided in the embodiment of the present invention comprises:
[0082] The high-performance silicon-aluminum composite negative electrode material is dry-mixed with the second binder, and then roll-pressed to obtain a negative electrode sheet. The negative electrode sheet is a thin sheet dry electrode, which can be directly used to assemble a battery, or the thin sheet dry electrode can be hot-pressed onto a current collector and then used to assemble a battery. The thickness of the thin sheet dry electrode can be between 40 μm and 120 μm.
[0083] The mass of the second binder accounts for 0.5% to 5% of the mass of the high-performance silicon-aluminum composite negative electrode material.
[0084] The second adhesive is polytetrafluoroethylene (PTFE), which only needs to be heated to 80° C. to 100° C. to have excellent bonding properties.
[0085] The dry mixing method specifically includes: placing the high-performance silicon-aluminum composite negative electrode material and the second binder in a ball mill at 80°C to 100°C, setting the rotation speed to 150rpm to 200rpm, ball milling for 7 minutes to 10 minutes, stopping the ball milling for 3 minutes to 5 minutes, and then continuing the ball milling for 7 minutes to 10 minutes, repeating the ball milling process for a total of 0.5 hours to 1 hour. During the ball milling process, zirconium oxide balls are added as ball milling media, and the material-ball ratio is 20:1.
[0086] The negative electrode sheet containing the high-performance silicon-aluminum composite negative electrode material provided in the embodiment of the present invention can be used to assemble a lithium-ion battery. Under external pressure, during the charge and discharge process of the lithium-ion battery, the nano-silicon particles in the high-performance silicon-aluminum composite negative electrode material in the negative electrode sheet and the aluminum-containing compound will maintain close contact with each other due to alloying and dealloying, thereby gradually forming a whole.
[0087] Lithium-ion batteries include any one of liquid lithium-ion batteries, semi-solid lithium-ion batteries or all-solid lithium-ion batteries. The above-mentioned negative electrode plate is preferably used in an all-solid lithium-ion battery.
[0088] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the high-performance silicon-aluminum composite negative electrode material of the present invention are respectively described below with multiple specific examples.
[0089] Example 1
[0090] This embodiment provides a preparation process of a high-performance silicon-aluminum composite negative electrode material, and the specific process is as follows.
[0091] The particle size D 50 200nm nano-silicon particles with a particle size D 50A total of 400 mg of 50 μm aluminum powder was placed in a ball mill for low-speed ball milling to obtain a high-performance silicon-aluminum composite negative electrode material. During the ball milling process, zirconium oxide balls were used as the ball milling medium, and the material-to-ball ratio was 20:1.
[0092] Among them, the mass ratio of nano-silicon particles to aluminum powder is 6:4.
[0093] The rotation speed of the low-speed ball mill is 150 rpm. The ball milling is performed for 7 minutes, then stopped for 3 minutes and then continued for 7 minutes. This ball milling process is repeated for a total of 1 hour.
[0094] The negative electrode sheet was prepared using the high-performance silicon-aluminum composite negative electrode material prepared in Example 1, and the specific process was as follows:
[0095] The high-performance silicon-aluminum composite negative electrode material of Example 1 and the binder polytetrafluoroethylene were placed in a ball mill at a mass ratio of 99:1, with a rotation speed of 150 rpm, and the ball milling was continued for 7 minutes after stopping for 3 minutes, and the ball milling process was repeated for a total of 2 hours to obtain a dry mixed block. In the ball milling process, zirconium oxide balls were used as ball milling media, and the material-ball ratio was 20:1.
[0096] The dry mixed block was roll-pressed to obtain a thin sheet dry electrode with a thickness of 60 μm.
[0097] The thin sheet of dry-process electrode is hot pressed onto the current collector copper foil to obtain the negative electrode sheet 1.
[0098] Then transfer it to a glove box filled with high-purity argon atmosphere for standby use.
[0099] Example 2
[0100] This embodiment provides a preparation process of a high-performance silicon-aluminum composite negative electrode material, and the specific process is as follows.
[0101] Biphenyl is dissolved in dimethyltetrahydrofuran to form a biphenyl-dimethyltetrahydrofuran solution with a concentration of 1 mol / L.
[0102] Metallic lithium is dissolved in a 1 mol / L biphenyl-dimethyltetrahydrofuran solution to obtain a pre-lithiation solution; wherein the molar ratio of metallic lithium to biphenyl is 1:1.
[0103] 270 mg of aluminum powder was added into 30 ml of the pre-lithiation solution, and the mixture was mechanically mixed and stirred for 3 hours until it was evenly mixed to obtain a mixed solution.
[0104] The solid obtained after filtering the mixed solution was washed 5 times with dimethyltetrahydrofuran, then vacuum dried at 80°C for 10 hours, crushed and sieved to obtain a particle size of D 50 It is a lithium aluminum alloy with a thickness of 50μm and the chemical formula is LiAl.
[0105] The particle size D 50 200nm nano-silicon particles with a particle size D 50 A total of 400 mg of 50 μm lithium aluminum alloy was placed in a ball mill for low-speed ball milling to obtain a high-performance silicon-aluminum composite negative electrode material.
[0106] The mass ratio of nano-silicon particles to aluminum powder is 4:6; the rotation speed of the low-speed ball mill is 150 rpm, the ball milling is performed for 7 minutes, the ball milling is stopped for 3 minutes, and the ball milling is continued for 7 minutes, and the ball milling process is repeated for a total of 1 hour.
[0107] The negative electrode sheet was prepared using the high-performance silicon-aluminum composite negative electrode material prepared in Example 2, and the specific process was as follows:
[0108] The high-performance silicon-aluminum composite negative electrode material of Example 2 and the binder polytetrafluoroethylene were placed in a ball mill at a mass ratio of 99:1, with a rotation speed of 150 rpm, and the ball milling was continued for 7 minutes after stopping for 3 minutes, and the ball milling process was repeated for a total of 2 hours to obtain a dry mixed block. During the ball milling process, zirconium oxide balls were used as ball milling media, and the material-ball ratio was 20:1.
[0109] The dry mixed block was roll-pressed to obtain a thin sheet dry electrode with a thickness of 60 μm.
[0110] The thin sheet of dry-process electrode is hot pressed onto the current collector copper foil to obtain the negative electrode sheet 2.
[0111] High-purity argon atmosphere protection is required throughout the preparation process.
[0112] Example 3
[0113] The negative electrode sheet was prepared using the high-performance silicon-aluminum composite negative electrode material prepared in Example 1, and the specific process was as follows:
[0114] The high-performance silicon-aluminum composite negative electrode material of Example 1 and a binder are uniformly mixed in a mass ratio of 92:8, wherein the binder is a mixture of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:0.8, and an appropriate amount of N-methylpyrrolidone is added and pulped to prepare a slurry at room temperature.
[0115] The slurry was rolled onto copper foil with a coating thickness of 150 μm, placed in a vacuum drying oven, vacuum dried at 120°C for 12 hours, and cut into circular electrodes with a diameter of 14 mm to obtain negative electrode electrodes 3. The negative electrode electrodes 3 were then transferred to a glove box filled with a high-purity argon atmosphere for standby use.
[0116] Example 4
[0117] The negative electrode sheet was prepared using the high-performance silicon-aluminum composite negative electrode material prepared in Example 2, and the specific process was as follows:
[0118] The high-performance silicon-aluminum composite negative electrode material of Example 2 and a binder are uniformly mixed in a mass ratio of 92:8, wherein the binder is a mixture of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:0.8, and an appropriate amount of N-methylpyrrolidone is added and pulped to prepare a slurry at room temperature.
[0119] The slurry was rolled onto copper foil with a coating thickness of 150 μm, placed in a vacuum drying oven, vacuum dried at 120° C. for 12 hours, and cut into circular electrodes with a diameter of 14 mm to obtain negative electrode electrodes 4. The negative electrode electrodes 4 were then transferred to a glove box filled with a high-purity argon atmosphere for standby use.
[0120] In order to better illustrate the effect of the embodiment of the present invention, a comparative example is compared with the above embodiment.
[0121] Comparative Example 1
[0122] This comparative example provides a preparation process of a conventional silicon negative electrode sheet, which is the same as the preparation process of Example 1, except that nano silicon particles are used as the negative electrode active material, as described below.
[0123] The nano-silicon particles and the binder polytetrafluoroethylene were placed in a ball mill at a mass ratio of 99:1, with a rotation speed of 150 rpm, and the ball milling was repeated for 7 minutes, 3 minutes, and then 7 minutes. The ball milling process was repeated for a total of 2 hours to obtain a dry mixed block. During the ball milling process, zirconium oxide balls were used as the ball milling medium, and the material-ball ratio was 20:1.
[0124] The dry mixed block was roll-pressed to obtain a thin sheet dry electrode with a thickness of 60 μm.
[0125] The thin sheet of dry-process electrode is hot pressed onto the current collector copper foil to obtain the negative electrode sheet 5.
[0126] Then transfer it to a glove box filled with high-purity argon atmosphere for standby use.
[0127] Comparative Example 2
[0128] This comparative example provides a process for preparing a negative electrode sheet, which is specifically as follows.
[0129] (1) Preparation of negative electrode active material: Nano-silicon particles, solid electrolyte Li6PS5Cl (LPSC) and conductive carbon are mixed in a certain mass ratio of 6:1:3 to obtain silicon negative electrode active material.
[0130] (2) A negative electrode sheet 6 was prepared by using silicon negative electrode active material and adopting the same negative electrode sheet preparation method as in Example 1.
[0131] Comparative Example 3
[0132] This comparative example provides a process for preparing a negative electrode sheet, which is specifically as follows.
[0133] (1) Preparation of negative electrode active material. The difference from Example 2 is that 270 mg of aluminum powder is added to 1 mL of pre-lithiation solution. The other processes of preparing materials are the same as those in Example 2 to obtain silicon negative electrode active material.
[0134] (2) A negative electrode sheet 7 was prepared by using the negative electrode active material in the same manner as in Example 2.
[0135] Comparative Example 4
[0136] This comparative example provides a process for preparing a negative electrode sheet, which is specifically as follows.
[0137] (1) Preparation of negative electrode active material. The difference from Example 2 is that 270 mg of aluminum powder is added to 5 mL of pre-lithiation solution. The other processes of preparing materials are the same as those in Example 2 to obtain silicon negative electrode active material.
[0138] (2) A negative electrode sheet 8 was prepared by using the negative electrode active material in the same manner as in Example 2.
[0139] Comparative Example 5
[0140] This comparative example provides a preparation process of a silicon-aluminum composite negative electrode material, which is different from Example 2 in that the particle size of the lithium-aluminum alloy used is 1 μm, and the other preparation processes are the same as Example 2.
[0141] The negative electrode plate was prepared using the silicon-aluminum composite negative electrode material prepared in Comparative Example 5, and the specific process was the same as that in Example 2, and finally a negative electrode plate 9 was obtained.
[0142] Comparative Example 6
[0143] This comparative example provides a preparation process of a silicon-aluminum composite negative electrode material, which is different from Example 2 in that the particle size of the lithium-aluminum alloy used is 100 μm, and the other preparation processes are the same as Example 2.
[0144] The negative electrode sheet was prepared using the silicon-aluminum composite negative electrode material prepared in Comparative Example 6, and the specific process was the same as that in Example 2, and finally a negative electrode sheet 10 was obtained.
[0145] Comparative Example 7
[0146] This comparative example provides a preparation process of a silicon-aluminum composite negative electrode material, which is different from Example 2 in that low-speed ball milling is not used, but ball milling is performed at a speed of 650 rpm for 2 hours, with a material-to-ball ratio of 20:1. The other preparation processes are the same as Example 2.
[0147] The negative electrode sheet was prepared using the silicon-aluminum composite negative electrode material prepared in Comparative Example 7, and the specific process was the same as that in Example 2, and finally a negative electrode sheet 11 was obtained.
[0148] The negative electrode sheets prepared in Examples 1-2 and Comparative Examples 1-7 were assembled into all-solid-state lithium-ion batteries and tested as follows:
[0149] The assembly process of all-solid-state lithium-ion batteries is a conventional method, specifically:
[0150] Preparation of positive electrode sheet: 140 mg of lithium nickel cobalt manganese oxide, 60 mg of solid electrolyte Li6PS5C l (LPSC) and 2 mg of polytetrafluoroethylene binder were placed in a ball mill at a speed of 150 rpm, and the ball milling was stopped for 7 minutes, then stopped for 3 minutes and then continued for 7 minutes, and the ball milling process was repeated for a total of 2 hours to obtain a dry mixed block. During the ball milling process, zirconia balls were used as the ball milling medium, and the material-ball ratio was 20:1.
[0151] The dry mixed block was roll-pressed to obtain a thin sheet dry electrode with a thickness of 150 μm.
[0152] The thin sheet of dry-process electrode is hot-pressed onto the current collector aluminum foil to obtain the positive electrode sheet.
[0153] High-purity argon atmosphere protection is required throughout the preparation process.
[0154] Assembly of all-solid-state lithium-ion battery: 80 mg of solid electrolyte Li6PS5C l (LPSC) powder was spread flat in the mold battery liner and cold pressed at a pressure of 200 MPa for 1 minute. Then, the negative electrode sheets prepared in Examples 1-2 and Comparative Examples 1-7 were respectively attached to one side of the above-mentioned solid electrolyte layer, and the prepared positive electrode sheets were attached to the other side of the solid electrolyte layer, and re-pressed at a pressure of 370 MPa for 3 minutes. Finally, they were placed in a stainless steel bracket and the screws were tightened to obtain all-solid-state lithium-ion batteries using the negative electrode sheets of Examples 1-2 and Comparative Examples 1-7, respectively.
[0155] The test process of all-solid-state lithium-ion battery: using Xinwei tester, set the charge cut-off voltage to 4.3V, the discharge cut-off voltage to 2.0V, and perform constant current charge and discharge test at 0.5C rate. Test the first week discharge capacity, first week coulomb efficiency and capacity retention rate after 50 cycles. The test data are detailed in Table 1.
[0156] The cycle curves of the all-solid-state lithium-ion batteries of Test Example 1, Example 2 and Comparative Example 2 are as follows: Figure 2 As shown, it can be seen that the cycle performances of Example 1 and Example 2 are both better than that of Comparative Example 2, and the cycle performance of Example 2 is the best.
[0157] The comparison chart of the first cycle coulombic efficiency and the capacity retention rate after 50 cycles of the all-solid-state lithium-ion batteries of test examples 1-2 and comparative examples 1-7 is as follows: Figure 3 shown.
[0158] Example 1 SEM image of the surface of the negative electrode of the all-solid-state lithium-ion battery after 50 cycles, as shown in Figure 4 As shown, it can be seen that after 50 cycles of Example 1, the surface flatness of the negative electrode plate is better and the density is higher, indicating that the contact between the solid particles is better.
[0159] Comparative Example 2 SEM image of the negative electrode surface of the all-solid-state lithium-ion battery after 50 cycles, as shown in Figure 5 As shown, it can be seen that the surface granularity of the negative electrode plate of Comparative Example 2 after 50 cycles is obvious and loose, indicating that the gaps between solid particles are large and the solid-solid contact is poor.
[0160] Table 1 is a summary of the test data of the negative electrode sheets prepared in Examples 1-2 and Comparative Examples 1-7 and the assembled all-solid-state lithium-ion batteries.
[0161]
[0162] Table 1
[0163] From the test data in Table 1, we can see that the nano-silicon and aluminum-containing compounds (D 50 The silicon-aluminum composite negative electrode material (Examples 1-2) prepared by mixing the aluminum powder with the nano-silicon (Comparative Example 1), the ordinary composite nano-silicon (Comparative Example 2) and the silicon-aluminum composite negative electrode prepared by other scales / rotating speeds (Comparative Examples 5-7) has higher first-cycle coulomb efficiency and capacity retention rate. In particular, the lithium-aluminum alloy obtained by pre-lithiation of aluminum powder can significantly improve the performance. For example, Examples 2, Comparative Examples 3 and Comparative Examples 4 are all D 50 The 50um aluminum powder was pre-lithiated, and its performance was better than that of the sample without pre-lithiation (Example 1), and when the pre-lithiation amount was the largest, the prepared silicon-aluminum composite negative electrode material (Example 2) had the best performance.
[0164] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-performance silicon-aluminum composite negative electrode material, characterized in that: The high-performance silicon-aluminum composite negative electrode material comprises: an aluminum-containing compound, and nano silicon particles uniformly attached to a framework structure formed by the aluminum-containing compound; The aluminum-containing compound includes: aluminum powder and / or lithium aluminum alloy; The average particle size D of the aluminum-containing compound 50 Between 5μm and 60μm; The mass of the nano silicon particles accounts for 40% to 90% of the total mass of the high performance silicon-aluminum composite negative electrode material; The mass of the aluminum-containing compound accounts for 10% to 60% of the total mass of the high-performance silicon-aluminum composite negative electrode material; The high-performance silicon-aluminum composite negative electrode material is obtained by low-speed ball milling of the nano silicon particles and the aluminum-containing compound.
2. The high performance silicon-aluminum composite negative electrode material according to claim 1, characterized in that: The aluminum-containing compound is in the shape of one or more of a rod, a line or an irregular shape; The average particle size D of the nano silicon particles 50 1nm~200nm; The general chemical formula of the lithium aluminum alloy is Li x Al, where 0<x≤1; The average particle size D of the high performance silicon-aluminum composite negative electrode material 50 5μm~60μm; The low-speed ball milling includes: placing the nano-silicon particles and the aluminum-containing compound in a ball mill, ball milling at a speed of 150rpm to 200rpm for 7 minutes to 10 minutes, stopping the ball milling for 3 minutes to 5 minutes, and then continuing the ball milling for 7 minutes to 10 minutes, repeating the ball milling process, and ball milling for a total of 1 hour to 2 hours.
3. A method for preparing a high-performance silicon-aluminum composite negative electrode material according to any one of claims 1 to 2, characterized in that: The preparation method comprises: performing low-speed ball milling on nano silicon particles and aluminum-containing compounds to obtain a high-performance silicon-aluminum composite negative electrode material; Wherein, the aluminum-containing compound comprises aluminum powder and / or lithium aluminum alloy; the general chemical formula of the lithium aluminum alloy is Li x Al, wherein 0<x≤1; the lithium aluminum alloy is obtained by pre-lithiation treatment.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the nano silicon particles to the aluminum-containing compound is 4:6 to 9:1; The particle size D of the aluminum-containing compound 50 Between 5μm and 60μm; The rotation speed of the low-speed ball mill is 150 rpm to 200 rpm. The ball mill is performed for 7 to 10 minutes, and then the ball mill is stopped for 3 to 5 minutes, and then the ball mill is continued for 7 to 10 minutes. The ball milling process is repeated for a total of 1 to 2 hours.
5. The preparation method according to claim 3, characterized in that: The pre-lithiation treatment comprises: dissolving metallic lithium in an organic solvent to obtain a pre-lithiation solution; Adding aluminum powder to the pre-lithiation solution, mechanically mixing and stirring to obtain a mixed solution; The solid substance obtained after filtering the mixed solution is washed at least twice with dimethyltetrahydrofuran, and then vacuum dried at 80° C. to 100° C. for 8 to 12 hours to obtain the lithium aluminum alloy; The organic solvent is a biphenyl-dimethyltetrahydrofuran solution formed by dissolving biphenyl in dimethyltetrahydrofuran; the molar ratio of the metallic lithium to the biphenyl in the organic solvent is 1:2 to 1:0.5; The general chemical formula of the lithium aluminum alloy is Li x Al, where 0<x≤1; The particle size D of the lithium aluminum alloy 50 Between 5μm and 60μm.
6. A negative electrode plate, characterized in that: The negative electrode plate comprises the high-performance silicon-aluminum composite negative electrode material described in any one of claims 1-2.
7. A method for preparing the negative electrode sheet according to claim 6, characterized in that: The preparation method comprises: mixing the high-performance silicon-aluminum composite negative electrode material according to any one of claims 1 to 2 with a first binder and a solvent to form a negative electrode slurry, then coating the negative electrode slurry on a current collector, and sequentially baking, rolling, and slitting to obtain a negative electrode sheet; The first binder includes: one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), polyacrylic acid, polytetrafluoroethylene (PTFE), and polymethyl methacrylate (PMMA); The solvent includes: any one of N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); The current collector comprises: any one of copper foil, stainless steel foil, titanium foil or a flexible composite current collector.
8. A method for preparing the negative electrode sheet according to claim 6, characterized in that: The preparation method comprises: dry mixing the high-performance silicon-aluminum composite negative electrode material according to any one of claims 1 to 2 with a second binder, and then performing a roll pressing process to obtain a negative electrode sheet; The second binder includes polytetrafluoroethylene (PTFE).
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as described in claim 6 above, or the negative electrode sheet prepared by the preparation method as described in claim 7 above, or the negative electrode sheet prepared by the preparation method as described in claim 8 above.
10. The lithium ion battery according to claim 9, characterized in that: The lithium ion battery includes: a liquid lithium ion battery, a semi-solid lithium ion battery or an all-solid lithium ion battery.
Citation Information
Patent Citations
Porous silicon-based composite anode material for lithium ion battery and preparation method and application
CN105070894A
Silicon-loaded aluminum oxide and graphene composite material as well as preparation method and application thereof
CN118039849A
Preparation method for composite negative electrode material of lithium ion battery
CN1909266A
Negative electrode active material for lithium ion secondary battery, its manufacturing method, and negative electrode for lithium ion secondary battery
JP7040832B1
Cited By
Fast-charging aluminum negative electrode material based on stepped temperature lithiation and preparation method of fast-charging aluminum negative electrode material
CN121306990A